2015
DOI: 10.1128/jvi.01595-15
|View full text |Cite
|
Sign up to set email alerts
|

Th1/17 Polarization of CD4 T Cells Supports HIV-1 Persistence during Antiretroviral Therapy

Abstract: The ability to persist long term in latently infected CD4 T cells represents a characteristic feature of HIV-1 infection and the predominant barrier to efforts aiming at viral eradication and cure. Yet, increasing evidence suggests that only small subsets of CD4 T cells with specific developmental and maturational profiles are able to effectively support HIV-1 long-term persistence. Here, we analyzed how the functional polarization of CD4 T cells shapes and structures the reservoirs of HIV-1-infected cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 47 publications
11
92
0
Order By: Relevance
“…Our findings are consistent with those recently published by Lichterfeld's and Lewin's groups [64, 65] for peripheral blood CCR6 + T-cells. All these findings are in line with a model in which the CCR6-CCL20 axis plays a critical role HIV latency establishment in resting CD4 + T-cells [89] and support the need for early intervention to block HIV infection of CCR6 + T-cells.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings are consistent with those recently published by Lichterfeld's and Lewin's groups [64, 65] for peripheral blood CCR6 + T-cells. All these findings are in line with a model in which the CCR6-CCL20 axis plays a critical role HIV latency establishment in resting CD4 + T-cells [89] and support the need for early intervention to block HIV infection of CCR6 + T-cells.…”
Section: Discussionsupporting
confidence: 94%
“…We also demonstrated that blood CCR6 + T-cells with T CM and Th17 and/or Th1Th17 phenotypes were enriched in integrated HIV-DNA; and that HIV reactivation is induced more robustly in CCR6 + versus CCR6 − T M , T CM , and T EM , upon TCR triggering in the presence of ATRA. These findings are consistent with the concept that fractions of Th17 cells are long-lived [61, 62, 63 ] and support HIV reservoir persistence during ART [ 63 , 64, 65]. HIV uses the molecular machinery of the host cells for integration into specific sites [73].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The nonrestoration of GALT Th17 cells leads to significant damages of the intestinal barrier, thus allowing microbial translocation, a cause for chronic immune activation and occurrence of non-AIDS comorbidities during ART (3,6,33). Despite their dramatic depletion, long-lived Th17 cells contribute to HIV reservoir persistence during ART (34,35). Consistently, our group identified a subset of CCR6 + CCR4 -…”
Section: Introductionsupporting
confidence: 70%